2023
DOI: 10.1108/ijebr-03-2022-0214
|View full text |Cite
|
Sign up to set email alerts
|

The role of marketing agility and risk propensity in resilience and survival of eastern European immigrant entrepreneurs in Denmark

Abstract: PurposeWhile extant research has increasingly examined minority entrepreneurs, less attention has been paid to Eastern European immigrant entrepreneurs and the role that marketing agility and risk propensity play in their resilience and survival in Nordic countries. This paper aims to highlight the importance of these factors for Eastern European immigrant entrepreneurs in the developed Nordic economy of Denmark.Design/methodology/approachThis paper adopts the dynamic capabilities view as a theoretical framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…These are important aspects that may help to explain how SMEs become more resilient through the development of such capabilities. In researching resilience and DCs, (Golgeci et al, 2023) also found that "leveraging multiple networks" enabled SMEs to survive the pandemic, and thus has synergy with several other studies cited above.…”
Section: Literature Review and Underpinning Theoretical Frameworkmentioning
confidence: 70%
See 1 more Smart Citation
“…These are important aspects that may help to explain how SMEs become more resilient through the development of such capabilities. In researching resilience and DCs, (Golgeci et al, 2023) also found that "leveraging multiple networks" enabled SMEs to survive the pandemic, and thus has synergy with several other studies cited above.…”
Section: Literature Review and Underpinning Theoretical Frameworkmentioning
confidence: 70%
“…, 2022, p. 1355), provide an analysis of different “configurations of DC dimensions”) and specifically the way in which these configurations enhance SMEs' “marketing and technological capabilities.” These are important aspects that may help to explain how SMEs become more resilient through the development of such capabilities. In researching resilience and DCs, (Golgeci et al. , 2023) also found that “leveraging multiple networks” enabled SMEs to survive the pandemic, and thus has synergy with several other studies cited above.…”
Section: Literature Review and Underpinning Theoretical Frameworkmentioning
confidence: 84%
“…Nevertheless, the exact percentage of firms with ethnic minority ownership that constitute being termed "family businesses" is not clear. However, following generations of migration and degrees of embeddedness into various nations' societies, a multi-cultural marketplace has existed for some time (Kloosterman, 2010;Demangeot and Sankaran, 2012;Jones et al, 2014;Golgeci et al, 2023). These patterns of migration, embeddedness and the creation of a multi-cultural marketplace have provided opportunities for entrepreneurs from respective ethnic minority backgrounds, including those operating in clusters of businesses typical of the restaurant sector featuring in this investigation (Ram et al, 2000a(Ram et al, , b, 2001Abdullah et al, 2009;Razzak et al, 2023).…”
Section: Introductionmentioning
confidence: 93%
“…However, following generations of migration and degrees of embeddedness into various nations' societies, a multi-cultural marketplace has existed for some time (Kloosterman, 2010; Demangeot and Sankaran, 2012; Jones et al. , 2014; Golgeci et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic affiliation to shared social, cultural and psychological ties are intangible action resources that contribute to innovation and novelty (Lounsbury et al, 2019). Leveraging multiple social networks and particularly the “refugee family” as a resource can not only support venture start‐ups (Sandberg et al, 2019; Zehra & Usmani, 2023) but also mitigate risks and ensure survival of business (Golgeci et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%